Relações socioambientais resultantes da implantação de um parque urbano - Nesello, Graziela Bristot (2021)
The urban parks are green areas, equipped with equipment for recreation and leisure activities within urban structures (KLIASS, 1993). Thus, the Lago Dourado Park in Dois Vizinhos, was born as a containment basin to minimize the environmental impacts caused by the occupation of areas of permanent preservation, waterproofing of the soil and urbanization, which caused flooding in parts of the town. Despite not being equipped with infrastructure, the population has developed a “sense of belonging”, giving notoriety to the space and demanding that the public authorities adapt it. Unable to raise funds due to lack of regulation, in 2017 a partnership with the “Allotment Portal do Lago” subsidized a major revitalization and building of the main structures, which ended up bringing to the area, an “elitization” of the surroundings with the real estate valuation and segregation space. Only in December 2020, through the Law No. 2.441/2020, said Lake was recognized as one of the nucleus of the “Dois Vizinhos Municipal Natural Park”, making it possible to provide government funds. In this sense, users point out as deficiencies: security, tranquility, quality of green areas, space for recreation and equipment for sports practice. Thus, it is necessary an intense work to improve it, making it possible to carry out many studies that can still be carried out in the area in order to disseminate and deepen socio, economic and environmental practices for the same, seeking its consolidation in space, preservation and quality of life of residents/users.